Aquaporin 1 mediates early responses to osmotic stimuli in endothelial cells via the calmodulin pathway. Issue 1 (24th November 2020) - Jiang, Yong; Wang, Chengqi; Ma, Rui; Zhao, Ying; Ma, Xinyue; Wan, Jiaxin; Li, Chunxiang; Chen, Fanghao; Fang, Fang; Li, Mingguang
Abstract : The aquaporins (AQPs) are a family of integral membrane proteins which play critical roles in controlling transcellular water movement in various tissues throughout the body. AQP1 helps mediate the cellular response to osmotic stress and tissue water permeability. However, the mechanism by which AQP1 mediates changes in cell volume is not completely clear. Here, we investigated how AQP1 responds to and controls cell volume upon osmotic stimuli during the early phase after the immediate response. Cells overexpressing AQP1 were exposed to hypotonic or hypertonic medium in the presence or absence of staurosporine or W‐7 hydrochloride, and fluorescence imaging was performed at 0, 5, 10, and 15 min later. Osmotic stimuli induced redistribution of AQP1 into the cell membrane, hypotonic stimuli caused cell enlargement, and hypertonic stimuli induced a reduction in cell size, which was blocked by T157A/T239A mutations. Changes in cell size induced by osmotic stimuli were blocked by an antagonist of calmodulin kinase, W‐7 hydrochloride, but not by the PKC inhibitor staurosporine. These results suggest that calmodulin kinase regulates AQP1 activity during the early response to osmotic stimuli. Abstract : Upon exposure to osmotic stimuli, AQP1 is phosphorylated and translocates to the cell membrane. After the initial response, the Ca2+/CaMK2 pathway is activated to regulate membrane localization and the activity of AQP1, which leads to a change in cell size and adjustment to the environment. These changes are blocked by the calmodulin antagonist W‐7.